Complete genome sequence and comparative genomics of the golden pompano (Trachinotus ovatus) pathogen, Vibrio harveyi strain QT520 - Zhigang Tu; Hongyue Li; Xiang Zhang; Yun Sun; Yongcan Zhou (PeerJ, 2017)
Vibrio harveyi is a Gram-negative, halophilic bacterium that is an opportunistic pathogen of commercially farmed marine vertebrate species. To understand the pathogenicity of this species, the genome of V. harveyi QT520 was analyzed and compared to that of other strains. The results showed the genome of QT520 has two unique circular chromosomes and three endogenous plasmids, totaling 6,070,846 bp with a 45% GC content, 5,701 predicted ORFs, 134 tRNAs and 37 rRNAs. Common virulence factors, including ACF, IlpA, OmpU, Flagellin, Cya, Hemolysin and MARTX, were detected in the genome, which are likely responsible for the virulence of QT520. The results of genomes comparisons with strains ATCC 33843 (392 (MAV)) and ATCC 43516 showed that greater numbers genes associated with types I, II, III, IV and VI secretion systems were detected in QT520 than in other strains, suggesting that QT520 is a highly virulent strain. In addition, three plasmids were only observed in the complete genome sequence of strain QT520. In plasmid p1 of QT520, specific virulence factors (cyaB, hlyB and rtxA) were identified, suggesting that the pathogenicity of this strain is plasmid-associated. Phylogenetic analysis of 12 complete Vibrio sp. genomes using ANI values, core genes and MLST revealed that QT520 was most closely related to ATCC 33843 (392 (MAV)) and ATCC 43516, suggesting that QT520 belongs to the species V. harveyi. This report is the first to describe the complete genome sequence of a V. harveyi strain isolated from an outbreak in a fish species in China. In addition, to the best of our knowledge, this report is the first to compare the V. harveyi genomes of several strains. The results of this study will expand our understanding of the genome, genetic characteristics, and virulence factors of V. harveyi, setting the stage for studies of pathogenesis, diagnostics, and disease prevention.